2003
DOI: 10.1021/jm0210212
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Effects of Novel 2-Amino-3-naphthoylthiophenes as Allosteric Enhancers of the A1Adenosine Receptor

Abstract: The current study describes the synthesis and biological evaluation of a novel series of 2-amino-3-naphthoylthiophenes, with variable modifications at the 4- and 5-position of the thiophene as well as the naphthoyl ring. Allosteric enhancer activity was measured in several ways: (1) evaluating the effect on forskolin-stimulated cAMP accumulation in the presence of an A(1)-adenosine agonist (CPA) in Chinese hamster ovary (CHO) cells expressing the cloned human A(1)-adenosine receptor (hA(1)AR); (2) ability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…Furthermore, the degree of overestimation would be similar for both vehicle-and PD-81723-treated mice subjected to renal I/R. Detailed structure activity relationship studies (6,9) to develop a potent A 1 AR allosteric enhancer have been previously reported. The common structural theme that has emerged from these studies is that chemicals with a 2-amino-3-benzoylthiophene core are excellent A 1 AR allosteric enhancers.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, the degree of overestimation would be similar for both vehicle-and PD-81723-treated mice subjected to renal I/R. Detailed structure activity relationship studies (6,9) to develop a potent A 1 AR allosteric enhancer have been previously reported. The common structural theme that has emerged from these studies is that chemicals with a 2-amino-3-benzoylthiophene core are excellent A 1 AR allosteric enhancers.…”
Section: Discussionmentioning
confidence: 89%
“…Baraldi and coworkers [12] identified five compounds more potent than PD 81,723 (e.g. 23, 24, see Fig. (2)) in increasing radiolabeled agonist binding to both human and rat adenosine A 1 receptors.…”
Section: A 1 Arsmentioning
confidence: 99%
“…A 3 AR ligands appear to have found very interesting applications in cancer therapies, and the possibility that A 3 AR plays a role in the development of cancer has aroused considerable interest in recent years (Merighi et al, 2003;. The A 3 subtype has been implicated in regulation of the cell cycle, and both pro-and antiapoptotic effects have been reported, depending on the level of receptor activation (Jacobson, 1998;Merighi et al, 2005a;Kim et al, 2010;Gessi et al, 2007;Taliani et al, 2010;.…”
Section: A 3 Ar and Cancermentioning
confidence: 99%